The Papillomavirus E2 Proteins: Structure, Function, and Biology - Hegde, Rashmi S. (Annual Review of Biophysics, 2002)
▪ Abstract Nearly twenty years after the first high-resolution crystal structures of specific protein-DNA complexes were determined, the stereo-chemical basis for protein-DNA recognition remains an active area of investigation. One outstanding question is, how are proteins able to detect noncontacted sequences in their binding sites? The papillomavirus E2 proteins represent a particularly suitable group of proteins in which to examine the mechanisms of “indirect readout.” Coordinated structural and thermodynamic studies of the E2-DNA interaction conducted over the past five years are summarized in this review. The data support a model in which the electrostatic properties of the individual E2 proteins correlate with their affinities for intrinsically flexible or rigidly prebent DNA targets.
Keywords: electrostatics